Typical Wines of Chile: The Rise and Decline of Chacolí (1810-2015) [Vinos Típicos de Chile: Ascenso y Declinación del Chacolí (1810-2015)] - Cussen-Abud, F; Lacoste, P; Cofre-Silva, C (Universidad de Tarapaca, 2015)
This article examines the emergence, consolidation and decline of Chacolí, typical Chilean wine. Heir to the Spanish colonial tradition, the Chilean Chacolí was made from Uva País (called Mission in California), Muscat of Alexandria and landraces, especially Torontel (Yellow Muscat). In the last third of the nineteenth century, Chacolí represented 28% of Chilean wine production. This typical wine then began to decline, strongly criticized by European technocrats and their Chilean fans who denied any value wine varieties used and artisanal methods. Anyway, the Chacolí has remained latent in small segments of consumers, especially popular segments and peasants; moreover, since 1975 it claimed in Chacolí Festival, held annually in Doñihue, in the deep heart of the traditional province of Colchagua. © 2015, Universidad de Tarapaca. All rights reserved.